PERKEMBANGAN WAKAF DARI TRADISI MENUJU REGULASI (ZISWAF: Jurnal Zakat dan Wakaf, 2015)
Beginning of the emergence endowments can be seen from two assumptions. The first assumption states that the Kaaba was built by Adam, and the pillars established by the Prophet Ibrahim and Prophet Ismail, and then preserved by the Prophet Muhammad, it is thus the Kaaba is the first endowments known to man and used for religious purposes. While the second assumption states that the Prophet Abraham who built the Kaaba, it means endowments began in the time of Prophet Ibrahim, who has brought the teachings of monotheism. Endowments ordered by the Prophet comes from the prophetic vision and not follow the example of the implementation of the endowment implemented ancient Egyptians and Greeks and Romans. Later, the endowment was established in the community is carried out dynamically from a tradition that is to be amplified by the regulation, as practiced in Muslim countries. Regulation waqf positive impact for the wider benefit such as health care, education, social. Economic and others. Health services are provided through endowments-waqf hospital. Management of waqf with contextual regulation can also be used to develop the productive waqf property through commercial efforts and the results for social purposes.